MODEL COPING SKILLS BERBASIS METODE INQUIRY DISCOVERY UNTUK MENGURANGI STRESS KERJA DI ERA NEW NORMAL - Trisnowati, Eli; Ralasari, Trimega (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The aim of this research is to determine the condition of IKIP PGRI Pontianak employees in dealing with work stress. The type and form of this research is descriptive research in the form of action research. The data source is employees of IKIP PGRI Pontianak. The data analysis technique uses descriptive analysis. Based on the research results, it was concluded that coping skills based on the inquiry discovery method to reduce employee work stress can be applied well. The impact of implementing the coping skills model based on the inquiry discovery method to reduce work stress in employees is the emergence of employees' ability to overcome anxiety, boredom, low self-confidence, loss of concentration, low self-esteem and anxiety in the work environment